Implementation of digital CSA reaches 35,000 maize and wheat farmers across Mexico with data-driven agronomic insights - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Large-scale MasAgro program reaches up to 35,000 farmers with data-driven insights fed into “Agrotutor” mobile application –a one-stop CSA information service. Based on CCAFS science and tools, Agrotutor includes a dedicated module for data-driven CSA practice recommendations. The current module, in addition to existing demand for climate information and climate services by farmers and technicians, has helped create an enabling environment for implementing agroecological zoning and seasonal forecasts for more targeted and ahead-of-season recommendations.